Synthesis of 1,2-Dihydronaphthalene by Cyclization of Dilactone - S. Deshmukh, Sujata; Banerjee, Shubhra (Asian Journal of Chemistry, 2010)
1,2-Dihydronaphthaiene has been synthesised by acid cleavage and cyclisation in one step of dilactone, obtained from ferulic acid by its oxidative coupling.